The Influence of Ownership Structure, Capital Structure, Investment Opportunities on Dividend Policy and Company Value - Salju Salju; Sapar Sapar; Asrianti Asrianti (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to analyze and explain the influence of capital structure ownership structure and investment opportunities directly or indirectly on firm value mediated by dividend policy. This study uses an explanatory approach. The population in this study were companies listed in the Indonesian Sharia Stock Index (ISSI) for the period 2013 to 2017 which amounted to 361 companies, and a sample of 42 companies. The data analysis used for hypothesis testing is the structure equation modeling (SEM) technique through the AMOS program. The results of this study indicate that: (1) Ownership structure and investment opportunities directly have a positive and insignificant effect on dividend policy, while their effect on firm value shows that ownership structure has a negative effect and investment opportunities have a positive effect. (2) Capital structure has a positive and significant effect on dividend policy and firm value. (3) The dividend policy directly has a positive and significant effect on firm value. (4) The indirect effect through dividend policy as a mediating variable shows that ownership structure and investment opportunities have a positive but not significant effect on firm value through dividend policy, while capital structure has a positive and significant effect on firm value through dividend policy. The findings of this study are the higher the ratio of ownership of the capital structure, and investment opportunities will tend to increase the ratio of dividend policy and firm value. However, there is a need for an increase in dividend policy because the role of dividend policy in Indonesian Sharia Stocks is still not strong in mediating institutional ownership structure and investment opportunities towards increasing firm value.